Relationship of Perceived Social Support and Self-actualization with Life Expectancy in the Elderly in Tehran - Marzieh Najafi; Ahmad Baseri (Hamadan University of Medical Sciences, 2018)
Background and Objective: Given that the elderly population has been increasing in recent years in Iran, studying their life expectancy and its related factors is necessary. Thus, we aimed to examine the relationship of perceived social support and self-actualization with life expectancy in the elderly of Tehran city. Materials and Methods: This descriptive correlational study was conducted on 200 elderly (nursing home residents and non-residents) of Tehran in 2016. The participants were selected using the convenience sampling method. Maslow's self-actualization, Miller's life expectancy, and Norbeck's perceived social support questionnaires were used for data collection. Then, the data were analyzed by using Pearson correlation coefficient and regression analysis in SPSS, version 20. Results: We found a significant positive relationship between perceived social support and life expectancy, self-actualization and life expectancy, as well as self-actualization and perceived social support in the elderly of Tehran (P<0.05). Also, the results of regression analysis showed that perceived social support and self-actualization had a direct effect on life expectancy. The results also revealed that the effect of perceived social support on life expectancy in nursing home residents was more than in non-residents. Moreover, the effect of self-actualization on life expectancy in non-resident elderlies was stronger than in nursing home residents (P<0.05). Conclusion: Findings of this study suggest that providing suitable grounds for quality improvement and promoting and creating perceived social support and self-actualization in the elderly can enhance their life expectancy.